2021
DOI: 10.13057/biodiv/d220960
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, biomass, covers, and NDVI of restored mangrove forests in Karawang and Subang Coasts, West Java, Indonesia

Abstract: Abstract. Suwanto A, Takarina ND, Koestoer RH, Frimawaty E. 2021. Diversity, biomass, covers, and NDVI of restored mangrove forests in Karawang and Subang Coasts, West Java, Indonesia. Biodiversitas 22: 4115-4122. Indonesia has been recognized as the country with greatest diversity of mangrove species with significant amount of carbon sink and biomass. In few recent decades, mangrove forests have been deforested significantly. One of the solutions to deal with mangrove deforestation is through restoration. Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
9
0
5
Order By: Relevance
“…Keberlangsungan dari jenis ini diperkirakan masih akan terus berlanjut, jika dilihat dari regenerasinya yang mengisi setiap fase pertumbuhan tanaman mangrove di lokasi ini. Hal ini dikarenakan tingkat adaptasi yang tinggi dari A. marina terhadap perairan dengan kondisi ekstrim, antara lain salinitas tinggi dan kondisi substrat berlumpur, serta sistem perakaran yang unik yang disebut pneumatophore (Suwanto et al, 2021).…”
Section: B Lokasi Rehabilitasi Mangrove Umur 5 Tahun (R5)unclassified
See 2 more Smart Citations
“…Keberlangsungan dari jenis ini diperkirakan masih akan terus berlanjut, jika dilihat dari regenerasinya yang mengisi setiap fase pertumbuhan tanaman mangrove di lokasi ini. Hal ini dikarenakan tingkat adaptasi yang tinggi dari A. marina terhadap perairan dengan kondisi ekstrim, antara lain salinitas tinggi dan kondisi substrat berlumpur, serta sistem perakaran yang unik yang disebut pneumatophore (Suwanto et al, 2021).…”
Section: B Lokasi Rehabilitasi Mangrove Umur 5 Tahun (R5)unclassified
“…Hal ini dikarenakan kegiatan rehabilitasi mangrove di negaranegara Asia Tenggara terutama difokuskan pada penanaman satu atau dua spesies, khususnya Rhizophora atau red mangrove (Malik et al, 2019;Harefa et al, 2022). Jenis Rhizophora lebih disukai karena kemampuan spesies ini untuk melindungi daerah pesisir dari erosi, gelombang tinggi, dan badai, serta bibitnya mudah dikumpulkan di sekitar areal restorasi (Malik et al, 2020;Suwanto et al, 2021). Selain itu, pemilihan jenis R. mucronata sebagai jenis yang ditanam pada awal kegiatan rehabilitasi karena jenis ini memiliki akar berbentuk batang (akar tunggang) yang cocok untuk ditanam di tanah berlumpur yang kurang stabil (Eddy et al, 2019).…”
Section: B Lokasi Rehabilitasi Mangrove Umur 5 Tahun (R5)unclassified
See 1 more Smart Citation
“…Mangroves are one of the important biological resources for Indonesia's coastal areas and are present in almost all coastal areas in the Indonesian Archipelago, ranging from Sumatra in the West to Papua Islands in the East. Indonesia alone comprises one-fifth of the global total mangrove area (Leal and Spalding 2022) and has 47 true mangrove species, representing a higher species diversity than any other country in the world (Suwanto et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These studies used a lot of different methods to estimate biomass. Many authors confirmed that the aboveground tree biomass was highly dependent on the stem diameter (D1.3) and proposed a onefactor correlation function of ln(AGB) = c + α ln (DBH) (Zhang et al 2013;Zianis and Mencuccini 2004;Suwanto et al 2021). Some authors affirmed that to obtain better results, the estimate of the aboveground biomass should also take into account the tree height (Hvn).…”
Section: Introductionmentioning
confidence: 99%